Hydrogen fuel cell: Parametric analysis of their stockpiling and different types. (2023) - Lokhande, Atharva A.; Rathore, Vaidant; Patel, Rushil; Dudhate, Rushikesh; Kulkarni, Kaustubh
Abstract: The concerns of toxic substances generated by traditional gasoline cars have spurred the intellectual world to search for environmentally friendly alternative energy sources. We do, however, have a variety of controllable energy sources, the best of which being hydrogen as a principal energy source for vehicles. Hydrogen, similar electrically, is a form of energy capable of transmitting large amounts of energy. Locally available hydrogen accumulating in vehicles is a major factor to consider when planning power module vehicles. These survey focuses at the latest developments in hydrogen power module engines to evaluate if hydrogen may be utilized as a viable fuel for transportation. An energy unit is a gas- and oxidant-reacting electrochemical device that creates electricity. Anodes split the cation and anion in the reactant, as well as the electrolytes, to transfer power. In power devices, ecologically responsible reactants are used, and water is created as a consequence of the process. Hydrogen is one of the most efficient power carriers available, the power device may produce additional stream (DC) capability to power the electric vehicle. Combining a hydrogen energy unit with batteries, as well as the control system and procedures, can result in a conservative creamer car.